2012
DOI: 10.1111/j.1476-4431.2012.00792.x
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of acute moderate hyperglycemia on traditional and thromboelastometry coagulation parameters in healthy adult horses

Abstract: Acute, moderate hyperglycemia in healthy adult horses does not have a detectable effect on coagulation based on evaluated parameters. Jugular catheter placement results in a transient increase in thrombin generation as determined by increased TAT concentrations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
19
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(19 citation statements)
references
References 67 publications
(115 reference statements)
0
19
0
Order By: Relevance
“…In an animal study, acute moderate hyperglycemia (10.0–13.3 mmol/L) maintained for 6 hours did not show a detectable influence on blood coagulation as measured by ROTEM. [25] In an in vivo study, platelets and endothelial cells were not activated during 6 hours of hyperglycemia with concentrations of 11.1 and 16.7 mmol/L in healthy volunteers. [26] In contrast, hyperglycemia produced increases in tissue factor procoagulant and platelet activity in healthy volunteers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In an animal study, acute moderate hyperglycemia (10.0–13.3 mmol/L) maintained for 6 hours did not show a detectable influence on blood coagulation as measured by ROTEM. [25] In an in vivo study, platelets and endothelial cells were not activated during 6 hours of hyperglycemia with concentrations of 11.1 and 16.7 mmol/L in healthy volunteers. [26] In contrast, hyperglycemia produced increases in tissue factor procoagulant and platelet activity in healthy volunteers.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, other studies were performed about 6 or 24 hours after the hyperglycemic condition. [2527] Therefore, there is a possibility that our study may not reflect the glucose effect on the coagulation cascade during 6 or 24 hours. Second, we evaluated only the hyperglycemic effect on blood coagulation.…”
Section: Discussionmentioning
confidence: 99%
“…Three hours before study onset, catheters (14 gauge 5.25 inch) were placed aseptically in both jugular veins, 1 for glucose and insulin sample collection, and 1 for endotoxin and dextrose infusion. A 3‐hour time lapse was allowed between catheter placement and study initiation because a previous study showed that placement of jugular catheters caused a transient increase in TAT . Baseline blood samples were collected immediately before initiation of infusions.…”
Section: Methodsmentioning
confidence: 99%
“…Methods for initiation and maintenance of controlled hyperglycemia in the GLU‐LPS group were identical to those previously described . A 50% dextrose solution was diluted in saline to obtain a 20% solution.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation